LITERASI DAN MODEL MANAJEMEN KEUANGAN UMKM BERBASIS DIGITAL PADA UMKM-UMKM DI KABUPATEN BOALEMO PROVINSI GORONTALO - Fibriyanti S. Lakoro; Sukrianto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
UMKM in Boalemo Regency have become a concern in recent times, especially inrunning their business. The purpose of the research is to provide knowledge tocommunity groups/micro and small and medium enterprises (UMKM) aboutliteracy and digital-based UMKM financial management models, and to be able toincrease the participation of community groups/UMKM in managing UMKMthrough the provision of knowledge about digital-based management. Descriptiveresearch method with a qualitative approach.The results showed that UMKM inBoalemo District experienced problems in running their businesses, especiallyduring the pandemic due to the lack of government attention in helping UMKM in Boalemo District. The average UMKM in Boalemo Regency in the use of financialliteracy fully understands the development of digital-based UMKM, especially inincreasing income, even their education level in managing good financialmanagement and digitally still relies on manual recording. While the digital-basedUMKM financial management model is not in accordance with the targets andobjectives. This is evidenced by UMKM business actors who have not been able tomake financial reports. UMKM in Boalemo Regency have not been able to useinformation technology and social media, especially in utilizing digital basedfinancial management designs. This is because UMKM only rely on manualrecording.